Adjustment Costs, Inventories and Output - Leif Danziger (Kiel Institute for the World Economy (IfW), 2007)
This paper analyzes the optimal adjustment strategy of an inventory-holding firm facing price- and quantity-adjustment costs in an inflationary environment. The model nests both the original menu-cost model that allows production to be costlessly adjusted, and the later model that includes price- and quantity-adjustment costs, but rules out inventory holdings. The firm's optimal adjustment strategy may involve stockouts. At low inflation rates, output is inversely related to the inflation rate, and the length of time demand is satisfied decreases with the absolute value of the demand elasticity, the storage cost, and the real interest rate.
Keywords: D24; D21; L23; 330; Menu costs; Quantity-adjustment costs; Inventories; Output; Inflation; Produktion; Betriebliche Lagerhaltung; Anpassungskosten; Inflation; Theorie